A unified digital twin framework for shop floor design in industry 4.0 manufacturing systems. (January 2021) - Lee, Jay; Azamfar, Moslem; Bagheri, Behrad
Abstract: Digital Twin and Cyber Physical Systems (CPS) are gaining popularity due to their significant impacts on the realization of smart manufacturing within which data and information from different systems is used to increase self-awareness, self-predict, and self-configure functionalities. Throughout the integration of digital twins with CPS, intelligent virtual counterparts are created that represent the behavior of the physical systems and provide predictive insights for advanced decision making. This article provides a systematic framework to integrate digital twins of different perspectives of a shop floor design from unit level, system implementation, cyber-physical integration, and business application all together into an end-to end design solution. We propose a time machine approach to utilize the historical data into the process of digital twin design and implementation and provide a simplified approach to evaluate the suitability of different designs for a given set of tasks and applications.